Neutron capture 128Xe and 129Xe in the San Juan mass of the Campo del Cielo IAB iron meteorite: Evidence for a high fluence of thermalized neutrons. (9th July 2021) - Pravdivtseva, O.; Varela, M. E.; Meshik, A.; Campbell, A. J.; Saavedra, M.; Topa, D.
Abstract: The petrographic study of the San Juan A2 polished section demonstrated textural and compositional similarities with the Campo del Cielo IAB iron meteorite, with trace element abundances in metal following the pattern of bulk Campo del Cielo. Xenon, neon, and helium isotopic compositions have been measured in radial graphite rims, massive graphite inclusions, fine‐grained graphite aggregates, cliftonite, and platy graphite. Two silicate inclusions and two areas of metal were also analyzed. 3 He/ 4 He versus 4 He/ 21 Ne data for San Juan metal plot next to the values reported for the El Taco fragment of Campo del Cielo, supporting San Juan being a part of the Campo del Cielo meteorite shower. Based on the Ne isotopic composition of its components, and the observed correlation between 128 Xe and 129 Xe, the San Juan A fragment of Campo del Cielo was well shielded from the primary galactic cosmic ray high‐energy irradiation. Its size allowed the secondary neutrons to be fairly well thermalized, receiving an equivalent (normalized to the research reactor with highly thermalized neutron spectrum) fluence of thermal and epithermal neutrons of 6.6 × 10 17  n cm −2 . Considering 1.8 × 10 8  years single‐stage and constant exposure geometry irradiation history for Campo del Cielo, and assuming the identical neutron flux spectra for the research reactor and Campo del Cielo, the average thermal equivalent neutron flux for San Juan is about 1.2 × 10 2  n cm −2  s −1 . Xe isotopic composition in the radial graphite rims and platy graphite shows evidence of live 129 I in San Juan and is consistent with a mixture of iodine‐derived and tellurium‐derived Xe.